PROGRESSION OF RENAL DYSFUNCTION AND ANAEMIA IN PATIENTS WITH CHRONIC HEART FAILURE - N. S. Kirshina; L. T. Pimenov (Российский кардиологический журнал)
The study aimed to assess renal function and anaemia prevalence and severity in patients with chronic heart failure (CHF) of various functional classes (FC). In total, 115 patients (76 women, 39 men; mean age 60,4±1,2 years) with NYHA FC I-IV CHF were examined. Renal filtration was assessed by glomerular filtration rate, GFR (Cockroft-Gault formula) and creatinine clearance (Reberg-Tareev method). Circadian GFR rhythm was analysed. Renal excretion was assessed by N-acetyl-beta-Dhexosaminidase (NAH) activity in morning urine sample. Microalbuminuria (MAU) prevalence and severity, as well as anaemia prevalence, were also analysed. Renal dysfunction in CHF depended on FC and manifested in disturbed circadian GFR rhythm, reduced GFR, progressing MAU, and impaired renal excretion. Urinal NAG combined with inadequate GRF reduction was an early marker of renal dysfunction. The most severe renal dysfunction, including disturbed circadian GFR rhythm, were observed in patients with high CHF FC and significantly decreased hemoglobin and hematocrit levels. There was no independent association between renal function and hemoglobin level. NAH, as an early marker of renal excretory dysfunction, was observed even in CHF FC I-II, before glomerular dysfunction manifested itself. Anaemia was associated with CHF FC.